1996
DOI: 10.3109/01485019608988494
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Kinetics and Morphology Before and After Fractionation on Discontinuous Percoll Gradient for Sex Preselection: Computerized Analyses

Abstract: The multiple-layer discontinuous Percoll density gradient centrifugation procedure is being used for gender selection and several reports suggested separation efficiencies of over 77%. The mechanism involved in the separation of X- and Y-bearing sperm using this method seems to be the difference in sperm head dimensions or motility but supporting data are inconsistent. The specific aims of the study were to evaluate the head dimensions of sperm at the upper and lower fractions after the 8-layer Percoll gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
2
4
1
1
Order By: Relevance
“…Motility was significantly lower in sperm from fractions 1 (10.7 Ϯ 1.3), 2 (15.9 Ϯ 1.5), and 3 (31.3 Ϯ 2.7) compared to sperm from fraction 4 (62.0 Ϯ 4.3) (P Ͻ 0.001). In contrast, the abnormal forms percent was significantly higher in sperm from fractions 1 (81.6 Ϯ 1.7), 2 (75.5 Ϯ 1.8), and 3 (51.7 Ϯ 2.5) compared to sperm from fraction 4 (20.8 Ϯ 2.1) (P Ͻ 0.001), also consistent with previous reports (Pousette et al, 1986;Le Lannou and Blanchard, 1988;Pardo et al, 1988;Menkveld et al, 1990;Van der Zwalmen et al, 1991;Mortimer and Mortimer, 1992;Saad and Guerin, 1992;Huszar et al, 1993;Hall et al, 1995;Sukcharoen, 1995;Yue et al, 1995;Watkins et al, 1996;Yao et al, 1996;Golan et al, 1997;Angelopoulos et al, 1998;Lassalle et al, 1999).…”
Section: Resultssupporting
confidence: 90%
“…Motility was significantly lower in sperm from fractions 1 (10.7 Ϯ 1.3), 2 (15.9 Ϯ 1.5), and 3 (31.3 Ϯ 2.7) compared to sperm from fraction 4 (62.0 Ϯ 4.3) (P Ͻ 0.001). In contrast, the abnormal forms percent was significantly higher in sperm from fractions 1 (81.6 Ϯ 1.7), 2 (75.5 Ϯ 1.8), and 3 (51.7 Ϯ 2.5) compared to sperm from fraction 4 (20.8 Ϯ 2.1) (P Ͻ 0.001), also consistent with previous reports (Pousette et al, 1986;Le Lannou and Blanchard, 1988;Pardo et al, 1988;Menkveld et al, 1990;Van der Zwalmen et al, 1991;Mortimer and Mortimer, 1992;Saad and Guerin, 1992;Huszar et al, 1993;Hall et al, 1995;Sukcharoen, 1995;Yue et al, 1995;Watkins et al, 1996;Yao et al, 1996;Golan et al, 1997;Angelopoulos et al, 1998;Lassalle et al, 1999).…”
Section: Resultssupporting
confidence: 90%
“…Kaneko et al [21] suggested that the sperm separation with Percoll gradients was due to differences in the basis of sperm velocity sedimentation, not on the basis of their buoyant density. The sperm sedimentation velocity may be influenced by differences in sperm head size or motility [15,22] but, there was no difference between the sperm head dimensions in the top and bottom fractions [22], but in contrast to a research report by Cui and Matthews [23].…”
Section: Discussioncontrasting
confidence: 46%
“…These findings suggest the preferential processing of X‐ and Y‐chromosome‐bearing sperm by oocyte cytoplasm depending on the maturation state and support the hypothesis that X sperm show greater longevity and penetrate the majority of oocytes when they become ready for fertilization. Watkins et al (1996) revealed a tendency for X‐chromosome‐bearing sperm after 24 h of incubation to show higher longevity in motility, higher progression and hyperactivation when compared with Y‐chromosome‐bearing spermatozoa. It is not known whether this influences their longevity in vitro .…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon is not fully understood, however it may be attributed to events that occur before fertilization that favour selection of X‐ or Y‐chromosome‐bearing spermatozoa, events that occur after fertilization such as preferential development or survival of embryos of one sex or a combination of both (Kochhar et al 2001). Moreover, analysis of the X‐ and Y‐sperm populations have shown some morphological and functional differences, although it is not known if X‐ and Y‐bearing spermatozoa have the same viability in vitro (Sarkar et al 1984; Watkins et al 1996; Penfold et al 1998; Van Munster et al 1999).…”
Section: Introductionmentioning
confidence: 99%